Effect of enalapril maleate on ghrelin levels in metabolic syndrome in rats - Aygen, Bilge; Kucuksu, Mehmet; Aydin, Suleyman; Ozercan, Ibrahim Hanifi (Elsevier Science Inc, 2015)
We have explored how enalapril affects ghrelin levels in serum and renal tissues of rats with fructoseinduced MetS, using 5-week-old Wistar albino male rats weighing 220 + 20g. They divided into 5 groups: (i) control (CT), no fructose supplement fed on standard rat pellet and tap water for 60 days, (ii) metabolic syndrome (MetS) fed with 10% fructose for 60 days, (iii) rats after metabolic syndrome developed treated with enalapril over 30 days (MetS + E30), (iv) rats in which only enalapril was administered for 60 days (E60), and (v) MetS-treated with enalapril for 60 days (MetS + E60). Enalapril maleate was given at 20 mg/kg per day by gavage. Fasting serum insulin, uric acid, triglyceride, low-density lipoprotein cholesterol and total cholesterol levels were significantly higher, and the amount of high density lipoprotein cholesterol, and acylated and desacyl ghrelin levels was significantly lower in the MetS groups. Ghrelins were significantly lower in all 3 groups, which were administered enalapril than that of MetS and the control group. Immunohistochemical staining showed that the density of ghrelin was parallel to the serum levels of the peptide. Ghrelin immunoreactivity in the kidneys was of moderate density in the distal and collecting tubules, mild density in the proximal tubule and glomeruli, whereas the density decreased in the MetS group and other enalapril-treated groups. In conclusion, ghrelin levels in MetS groups were significantly lower than control group, and thus Enalapril treatment improves components of MetS and has direct effects on serum ghrelin levels that are independent of MetS. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Metabolic syndrome; Ghrelin; Enalapril